2010
DOI: 10.1093/nar/gkp1217
|View full text |Cite
|
Sign up to set email alerts
|

Human RECQL5β stimulates flap endonuclease 1

Abstract: Human RECQL5 is a member of the RecQ helicase family which is implicated in genome maintenance. Five human members of the family have been identified; three of them, BLM, WRN and RECQL4 are associated with elevated cancer risk. RECQL1 and RECQL5 have not been linked to any human disorder yet; cells devoid of RECQL1 and RECQL5 display increased chromosomal instability. Here, we report the physical and functional interaction of the large isomer of RECQL5, RECQL5β, with the human flap endonuclease 1, FEN1, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 57 publications
2
31
0
2
Order By: Relevance
“…Several of the RecQ helicases, including BLM [32], WRN [33], RECQL4 [34] and RECQ5β [35], have been found to stimulate the 5′-flap incision of FEN1. Hence, based on the physical interaction observed between hSuv3 and FEN1, we tested whether the interaction could modulate the catalytic activity of one or both of the proteins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several of the RecQ helicases, including BLM [32], WRN [33], RECQL4 [34] and RECQ5β [35], have been found to stimulate the 5′-flap incision of FEN1. Hence, based on the physical interaction observed between hSuv3 and FEN1, we tested whether the interaction could modulate the catalytic activity of one or both of the proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Helicase-independent stimulation of FEN1 activity has also been shown for WRN, BLM, RecQ4 and RecQ5 [3235]. The interaction between WRN and FEN1 has previously been proposed to be involved in initiation of recombination pathways at stalled replication forks by employing FEN1’s GEN activity [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, RECQL5 physically interacts with human Flap Endonuclease 1 (FEN1), which plays a critical role in the processing of Okazaki fragments during DNA replication and dramatically stimulates the rate of FEN1 cleavage on both 5′ flap and nicked DNA substrates (Speina et al , 2010). This raises the intriguing possibility that RECQL5, via stimulation of FEN1, could also coordinate the cleavage event needed to reset an uncoupled replication fork (Speina et al , 2010). Furthermore, RECQL5 can promote strand exchange on synthetic DNA structures that resemble a stalled replication fork.…”
Section: Role Of Recql5 In Dna Replication and Chromosomal Segregationmentioning
confidence: 99%
“…In humans, WRN, BLM, and RecQ5, the human homologues of yeast RecQ are an example of Fen1 stimulator (Brosh et al, 2001;Wang et al, 2005;Speina et al, 2010). Recently, it was shown that Dna2 and Pif1 can contribute to rapid nick formation by stimulating FEN1 (Henry et al, 2008).…”
Section: Speculations On the Presence Of Numerous Stimulators Of Dna2mentioning
confidence: 99%